Making smart manufacturing smarter – a survey on blockchain technology in Industry 4.0. Issue 10 (26th November 2021) - Zuo, Yanjun
ABSTRACT: Blockchain is distributed digital ledger technology that facilitates reliable and transparent transactions among the participants of a system. Blockchain has been applied to various manufacturing applications and helps to create an automatic, decentralised smart manufacturing system with a high level of efficiency and productivity. This paper presents a comprehensive survey on blockchain in Industry 4.0 – applications, architectures, techniques, and research challenges. We propose a blockchain reference architecture for smart manufacturing, which guides our discussions on applying the blockchain technology to various applications of the smart factory and smart supply chain.